Doing Ethnography of Policies against Sexual Violence: Perspectives for a Case Study in the Universities of Montreal - Farneti, Alice (Cahiers d'histoire, 2023)
This article discusses some of the problematics that inform the methodology of my ongoing doctoral research on policies against sexual violence in Montreal universities. First, I will argue that feminist activists in Quebec have been able to expose the institutional dimension of sexual violence in university. Then, I will then compare Dorothy Smith’s institutional ethnography approach with Sara Ahmed’s phenomenological approach to institutions to elaborate on the concept of lived experience as a starting point for the investigation of institutional regimes. In conclusion, I will engage with Nancy Naples’ outsider/insider debate to reflect on the multiplicity of divergent and contradicting perspectives in the field.